Nonischemic Priapism in Childhood: A Case Series and Review of Literature - Hacker, Hans-Walter; Schwoebel, Marcus G.; Szavay, Philipp O. (European Journal of Pediatric Surgery, 2018)
Introduction Nonischemic priapism (NIP) in childhood is a very rare affection. In the literature, patients with NIP are described mainly incidental after perineal trauma. Many of them underwent embolization of either internal pudendal artery or bulbocavernosal arteries.Patients and Methods We report on six boys between 4 and 13 years of age with NIP, treated at our institution between 2008 and 2014. Color Doppler ultrasound (CDU) was performed in all patients as emergency diagnostic evaluation. Patients were treated conservatively, including bed rest, local cooling, and perineal compression. History, etiological factors, clinical findings, diagnostics, and follow-up are presented.Results Out of the six patients, only one boy had a history of perineal injury with subsequent arteriocavernosal fistula, revealed in CDU. Five patients were circumcised, and one of them suffered from thalassemia minor, but no other underlying disease or etiological factors could be found. In all patients, normal to high blood flow velocities were detected in the cavernosal arteries. Detumescence started with nonoperative treatment within 24 hours in five boys and in one patient with recurrent priapism after 1 week. All six patients remained painless without evidence for an ischemic priapism. None of them suffered from relapse and further erections were observed during follow-up from 3 to 87 months.Conclusion In contrast to the literature, five out of six boys developed NIP without a previous perineal trauma. The etiology of idiopathic NIP in childhood remains unclear; however, circumcision may play a role as a conditional factor. One etiological thesis could be the release of the neurotransmitter nitric oxide after stimulation of the corpora cavernosa. Conservative treatment proved to be successful in all six patients. During a median follow-up of 55 months (3–87 months), none of the patients showed signs of erectile dysfunction.
Keywords: nonischemic priapism; etiology; treatment; childhood